Conservative surgical treatment with fertility preservation in a young adult with NTRK rearranged spindle cell neoplasm of the uterine cervix - Marco M. Bühler; Hanna Honcharova-Biletska; Chantal Pauli; Dimitrios Chronas; Kristina Bolten (Gynecologic Oncology Reports, 2023)
In depth molecular studies are constantly expanding our understanding and refining the classification of gynecological neoplasms. NTRK rearranged spindle cell neoplasms of the lower genital tract are an emerging entity, of particular interest due to possible targeted treatment with selective kinase inhibitors. Nonetheless, surgery remains the initial treatment of choice. We present the case of a 24-year-old patient suffering from a NTRK rearranged spindle cell neoplasm of the uterine cervix which was treated with a fertility preserving conservative surgical approach.